Behavior of wild tigers in captivity at the Central Zoo, Nepal - Nishan Pokhrel; Narayan Prasad Koju; Sandeepa Gautam; Randall C. Kyes (PLoS ONE, 2026)
The majority of tigers ( Panthera tigris ) maintained at the Central Zoo in Jawalakhel, Nepal represents rescues resulting from human-wildlife conflict situations. Their behavior in captivity can be influenced by a variety of factors including environmental and social variables such as visitor presence, sex of the tiger, and duration of captivity. In this study, we investigated how visitor presence, sex, and captivity duration influence the behavior pattern of captive tigers. Behavioral observations were conducted on four adult tigers (two males and two females) across summer and monsoon seasons using instantaneous scan sampling guided by a detailed ethogram and supported by CCTV recordings. Data were collected during both peak visiting hours and off-peak periods. Overall, the tigers exhibited high levels of inactivity, predominantly sleeping (43.7%) and resting (34.2%). Visitor presence significantly affected activity patterns of both male and female tigers (p < 0.001), marked by increased pacing and drinking behavior during peak hours. The off peak hours were dominated by resting and sleeping. Females tigers displayed more pacing and exploratory behaviors, while males were more sedentary. A recently rescued female (n = 1) exhibited higher level of play and exploration, whereas long-term captives showed elevated pacing and more repetitive and predictable routines (p < 0.001). Visitor presence, sex, and duration in captivity interactively shape the behavior expression and welfare indicators in these captive tigers. These findings highlight the importance of effective visitor management and environmental enrichment and play an important role in establishing welfare strategies to mitigate stress in captive tigers.